Sharia Economic Law Perspective On Online Meeting Premium Account Leasing - Muhamad Izazi Nurjaman; Sofian Al-Hakim; Iwan Setiawan; Doli Witro; Mualimin Mochammad Sahid (Muhammadiyah University Press, 2022)
In general, in leasing goods (ijarah ala al-a'yan) the object of the contract is the benefit that comes from tangible objects. However, it is different from renting a Zoom Meeting Premium account whose position is as application software. So that its position will have benefits if its use is collaborated with hardware as hardware. Meanwhile, if it is only the software that is being leased, how can the software have benefits as the object of an ijarah contract which is the benefit of an object. Therefore, this study will discuss the practice of renting a Zoom Meeting Premium account according to the perspective of sharia economic law. This research is a research that uses a descriptive case study method with an empirical juridical approach. The data analysis technique was carried out through three stages, namely data reduction, data presentation and conclusions. The results of this study find the fact that the position of Zoom Meeting is premium as an application software that is part of a computer program. While the computer program is part of the copyright in the form of intangible movable objects. So that there is the development of the object of the ijarah contract which is generally in the form of benefits derived from tangible objects which can also come from the benefits of intangible objects.